Accidental chlorophacinone exposure of lactating ewes: Clinical follow-up and human health dietary implications. (September 2020) - Moriceau, Meg-Anne; Lefebvre, Sébastien; Fourel, Isabelle; Benoit, Etienne; Rattner, Barnett A.; Lattard, Virginie
Abstract: Anticoagulant rodenticides are widely used for rodent control in agricultural and urban settings. Their intense use can sometimes result in accidental exposure and even poisoning of livestock. Can milk, eggs or meat derived from such accidently exposed animals be consumed by humans? Data on the pharmacokinetics of chlorophacinone in milk of accidently exposed ewes were used to estimate the risk associated with its consumption. Three days after accidental ingestion, chlorophacinone was detected in plasma of 18 ewes, with concentrations exceeding 100 ng/mL in 11 animals. Chlorophacinone was detected in milk on day 2 post-exposure and remained quantifiable for at least 7 days in milk of these 11 ewes. Concentrations in milk were much lower than in plasma and decreased quickly (mean half-life of 2 days). This study demonstrated dose-dependent mammary transfer of ingested chlorophacinone. Variation in prothrombin time (PT) on Day 3 suggested that some of the ewes that ingested chlorophacinone may have been adversely affected, but PT did not facilitate estimation of the quantity of chlorophacinone consumed. Using safety factors described in the literature, consumption of dairy products derived from these ewes after a one-week withdrawal period would pose low risk to consumers. Graphical abstract: Image 1 Highlights: Accidental chlorophacinone ingestion by dairy ewes led to its dose-dependent mammary transfer. Residue levels in milk were low and decreased rapidly (t1/2  = 2 days). Estimated "withdrawal period" for human consumption of milk was about 6 days. Risk to humans consuming this milk was seemingly low, even in a worst-case scenario.